Practical synthesis of 3, 3-substituted dihydroquinoxalin-2-ones from aryl 1, 2-diamines using the Bargellini reaction. Issue 39 (28th September 2016) - Alanine, Thomas A.; Stokes, Stephen; Scott, James S.
Graphical abstract: Highlights: Provides access to useful 3, 3-disubstituted dihydroquinoxalinones in good yields. The mild reaction conditions tolerate a variety of chemical functionalities. Complexity is readily incorporated on the saturated ring. Pyridine diamines can be used as well as o -phenylene diamines. The formation of regioisomers is rationalised mechanistically. Abstract: The reaction of aromatic 1, 2-diamines with trichloromethylcarbinols under mild, basic phase-transfer conditions provided expedient access to 3, 3-disubsituted quinoxalin-2(1 H )-ones in good to moderate yields. The use of unsymmetrical aryl diamines gave a regioisomeric mixture of products with the ratio shown to be dependent on the electronic nature of the aromatic substituents. 2, 3-Diaminopyridines could also be used, showing excellent selectivity for the dihydro[3, 2- b ]pyridopyrazin-2-one isomer.